2021
DOI: 10.1155/2021/3941648
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Dependence Structure and Risk Spillover of Internet Money Funds Based on C‐Vine Copula and Time‐Varying t‐Copula

Abstract: Internet money funds (IMFs) are the most widely involved products in the Internet financial products market. This research utilized the C-vine copula model to study the risk dependence structure of IMFs and then introduces the time-varying t-copula model to analyze the risk spillover of diverse IMFs. The results show the following: (1) The risks of Internet-based IMFs, bank-based IMFs, and fund-based IMFs have obvious dependence structure, and the degree of risk dependence among different categories of IMFs is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The application of liquidity risk results in portfolio research also needs further exploration. Besides, the literature [1][2][3][4][5][6][7][25][26][27] already proved the necessity of portfolio design, but whether the portfolio design of different IMFs can also follow similar portfolio ideas still needs further proof.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of liquidity risk results in portfolio research also needs further exploration. Besides, the literature [1][2][3][4][5][6][7][25][26][27] already proved the necessity of portfolio design, but whether the portfolio design of different IMFs can also follow similar portfolio ideas still needs further proof.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IMFs are the money market funds released by fund companies on Internet platforms and gather the idle funds of individual investors and then invest them with fund management companies (Ma et al (2021) [1]). IMFs have the advantages of convenience and reasonable return rates, attracting a wide range of investors.…”
Section: Introductionmentioning
confidence: 99%
“…In literature [10] from the analysis of the loan data of users on the credit platform, it is found that online credit is superior to traditional credit methods in cost control and the benefits it brings are higher than those of traditional credit business, so it is of practical significance to promote online credit. Literatures [11,12] adopt linear support vector machine classifier, combine genetic algorithm and particle swarm optimization to select parameters, and use discriminant analysis to identify the bankruptcy grade of bank customers. The research shows that this method can better identify bankrupt customers than the original model.…”
Section: Introductionmentioning
confidence: 99%
“…Internet money market funds (IMMFs), also known as Internet money funds, are Internet financial products with the broadest social participation. IMMFs usually gather idle funds of individual investors to obtain profit with the help of internet wealth management platforms [1][2] and have long been lucrative for shareholders and fund firms. Take the largest IMMF in China, Yu'E Bao, as an example; its scale was up to about 764.578 billion Yuan (approximately 120.19 billion dollars) as of the end of the third quarter of 2021.…”
Section: Introductionmentioning
confidence: 99%